2021
DOI: 10.1016/j.joca.2021.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-resolved nanometer-scale measurement of cartilage extracellular matrix mobility

Abstract: Objective: Tissues have complex structures, comprised of solid and fluid phases. Improved understanding of interactions between joint fluid and extracellular matrix (ECM) is required in models of cartilage mechanics. X-ray photon correlation spectroscopy (XPCS) directly measures nanometer-scale dynamics, and thus can provide insight into biofluid-biosolid interactions in cartilage. This study applies XPCS to evaluate dynamic interactions between intact cartilage and biofluids.Design: Cartilage biopsies were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…XPCS can provide meaningful information from samples with extremely low scattering intensities (Sheyfer et al, 2022;Lurio et al, 2021;Partain et al, 2021), but doing so requires averaging of XPCS results from hundreds or sometimes even thousands of repeating measurements to achieve the signalto-noise ratio (SNR) of g 2 sufficient for quantitative analysis (Zhang et al, 2021). To avoid prolonged X-ray exposure and mitigate the beam damage, such repeated measurements are usually performed on different locations of the sample, which makes the averaging of the results susceptible to spatial heterogeneity of the sample.…”
Section: Averaging Of Xpcs Resultsmentioning
confidence: 99%
“…XPCS can provide meaningful information from samples with extremely low scattering intensities (Sheyfer et al, 2022;Lurio et al, 2021;Partain et al, 2021), but doing so requires averaging of XPCS results from hundreds or sometimes even thousands of repeating measurements to achieve the signalto-noise ratio (SNR) of g 2 sufficient for quantitative analysis (Zhang et al, 2021). To avoid prolonged X-ray exposure and mitigate the beam damage, such repeated measurements are usually performed on different locations of the sample, which makes the averaging of the results susceptible to spatial heterogeneity of the sample.…”
Section: Averaging Of Xpcs Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that high molecular weight HA not only has the ability to suppress inflammation but also inhibits nitric oxide-induced apoptosis and dedifferentiation of articular chondrocytes in osteoarthritis (Peng et al, 2010;Partain et al, 2021). Therefore, HA may play an important role in downregulating the Il-1β expression and may be more efficient for aggrecan expression than PRF alone.…”
Section: Figurementioning
confidence: 99%